The Adoption of an AI Translation Software to Reduce Lexico-Grammatical Errors at Higher Education - Haryanti, Jevi; Sabartono, Ribut (Linguapedia, 2023)
This research study is to explore the perception of students majoring in English who are writing their thesis regarding the accuracy of Google Translate in reducing lexico-grammar errors among students at private universities in Jember, Indonesia. There were ( N = 6 ) student who were willing to participate in this study. Qualitative method and semi structured interviews were conducted to explore their feeling in depth with the students who were the respondents. The results showed that Google Translate could not reduce grammar errors, there were still some errors in student thesis writing. Students need to check the translation result and correct them. Google Translate help students revise their writing to produce good writing that is free from grammatical errors.